2020
DOI: 10.1080/16000889.2019.1695349
|View full text |Cite
|
Sign up to set email alerts
|

Airborne survey of trace gases and aerosols over the Southern Baltic Sea: from clean marine boundary layer to shipping corridor effect

Abstract: The influence of shipping on air quality over the Southern Baltic Sea was investigated by characterizing the horizontal and vertical distribution of aerosols and trace gases using airborne measurements in the summer of 2015. Generally, continental and anthropogenic emissions affected the vertical distribution of atmospheric pollutants, leading to pronounced stratification in and above the marine boundary layer and controlling the aerosol extinction. Marine traffic along the shipping corridor "Kadet Fairway" in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 96 publications
(116 reference statements)
0
11
0
Order By: Relevance
“…To the knowledge of the authors, no previous studies have reported on the effects of FSC on particle sizes and concentrations from atmospheric exhaust plume measurements. Furthermore, the results from direct emission measurements are divided in the literature: Zetterdahl et al (2016) reported that the stricter FSC limits reduce the particle size, but not the produced PNC pl , whereas studies such as Streibel et al (2017) found lower emission factors for PNC pl and larger particle size when using distillate fuels instead of HFO.…”
Section: Particle Number Size Distribution Of the Exhaust Plumesmentioning
confidence: 99%
See 1 more Smart Citation
“…To the knowledge of the authors, no previous studies have reported on the effects of FSC on particle sizes and concentrations from atmospheric exhaust plume measurements. Furthermore, the results from direct emission measurements are divided in the literature: Zetterdahl et al (2016) reported that the stricter FSC limits reduce the particle size, but not the produced PNC pl , whereas studies such as Streibel et al (2017) found lower emission factors for PNC pl and larger particle size when using distillate fuels instead of HFO.…”
Section: Particle Number Size Distribution Of the Exhaust Plumesmentioning
confidence: 99%
“…Photochemical aging changes the physical and chemical properties of the ship plume particles. The sulfur content in fuel affects SO 2 emitted from marine engines; nevertheless, Zetterdahl et al (2016) also measured reduced volatile organic compound (VOC) emissions related to a lower FSC. However, in contrast to decreased secondary aerosol (SA) precursor observations (SO 2 and VOC), Wu et al (2020) observed an increase in SA formation due to changing from residual fuel oils to distillate fuels.…”
Section: Photochemical Aging Of the Plumesmentioning
confidence: 99%
“…Because many ships run on residual fuels outside the SECAs 410 and switch to low-sulfur distillate fuels when entering them (Van Roy, W and Scheldeman, K., 2016;Lähteenmäki-Uutela et al, 2019), their lubrication oil can contain metals from previous residual fuel operation that can consequently be emitted in small amounts also during operation in SECAs. Recently, also Zanatta et al found a limited number of V-Fe particles in the marine boundary layer along ship lanes in the Baltic Sea using an aircraft-based SPMS (Zanatta et al, 2020).…”
Section: Assignment To Shipsmentioning
confidence: 97%
“…Because many ships run on residual fuels outside the SECAs 410 and switch to low-sulfur distillate fuels when entering them (Van Roy, W and Scheldeman, K., 2016;Lähteenmäki-Uutela et al, 2019), their lubrication oil can contain metals from previous residual fuel operation that can consequently be emitted in small amounts also during operation in SECAs. Recently, also Zanatta et al found a limited number of V-Fe particles in the marine boundary layer along ship lanes in the Baltic Sea using an aircraft-based SPMS (Zanatta et al, 2020).…”
Section: Assignment To Shipsmentioning
confidence: 97%